2022
DOI: 10.1002/jcp.30830
|View full text |Cite
|
Sign up to set email alerts
|

Noncoding RNAs in diagnosis and prognosis of graft‐versus‐host disease (GVHD)

Abstract: Allogeneic hematopoietic stem cell transplantation (allo‐HSCT) is a functional therapy for a plethora of hematologic malignancies and immune disorders. Graft‐versus‐host disease (GVHD), on the other hand, is one of the major complications ahead of a successful HSCT, contributing to transplant‐associated morbidity and mortality. Notably, little is known about the underlying mechanism of this event; therefore, exploring precise biomarkers and uncovering the molecular pathogenesis of GVHD is valuable for early di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 125 publications
0
3
0
Order By: Relevance
“…Several preclinical and clinical studies in various periods pre-and post-HSCT showed dysregulated miRNA levels and their function in massive immune responses leading to the development of GvHD [157,158]. A differently expressed miRNA profile appears to be a promising noninvasive tool for specific diagnosis and prediction of aGvHD occurrence (Figure 1).…”
Section: Microrna and Graft-versus-host Diseasementioning
confidence: 99%
“…Several preclinical and clinical studies in various periods pre-and post-HSCT showed dysregulated miRNA levels and their function in massive immune responses leading to the development of GvHD [157,158]. A differently expressed miRNA profile appears to be a promising noninvasive tool for specific diagnosis and prediction of aGvHD occurrence (Figure 1).…”
Section: Microrna and Graft-versus-host Diseasementioning
confidence: 99%
“…The role of non-coding RNAs, mainly microRNAs, in T-cell immunobiology is well established and is increasingly being explored in the context of hematopoiesis and allogeneic HSCT ( 105 , 106 ). Several microRNAs are emerging as important regulators of allogeneic T-cells and may prove to be highly sensitive and specific biomarkers for GVHD and useful targets for anti-GVHD oligonucleotide-based therapeutics ( 105 108 ).…”
Section: Epigenetic Regulation Of Hematopoietic Stem Cells Before And...mentioning
confidence: 99%
“…14 However, owing to the distinct microenvironments of various organs and tissues, the miRNAs associated with the disease also exhibit variations. 15,16 Consequently, it prompts the question of whether miRNA profiles also change in oral cGVHD patients and how these changes impact the disease.…”
Section: Introductionmentioning
confidence: 99%